Household Economy, Anxiety During The COVID-19 Pandemic And Economic Activity During The COVID-19 Pandemic - Hayati, Fitri (International Journal of Cultural and Social Science, 2022)
The COVID-19 pandemic has a big impact on people's economic activities where there is an increase in family expenditure; basic needs cannot be met until people do not want to go to public places or facilities such as markets, malls or restaurants. This study was conducted in Medan City in January-August 2021. The number of participants in this study was 1029 families. The results show went to Market for last Month as many as 230 families (22.4%) and did not go to the Market during the last Month, as many as 515 families (50%). Of the 284 families whose family needs were not met, they were less likely to go to the Market during the last Month than as many as 197 families (19.1%). The Medan City Government must provide comfort for the community in carrying out buying and selling activities in public places such as markets, malls and restaurants during the COVID-19 pandemic.